Properties And Performance Of Natural Rubber Latex (NRL) Band: A Scavenging Medium To Capture Microplastic Waste In Water - Mohd Sabri, Nur Shauqina (Universiti Sains Malaysia, 2022)
In recent years, the widespread presence of microplastics in the environment has become a significant challenge, especially to the marine system. The critical concerns are the ecotoxicological impact on marine ecosystems and the potential threat to human organs and tissues. This study was conducted to develop the microplastic waste capture in seawater using natural rubber latex (NRL) band via a surface capturing mechanism. In this study, we proposed that the rubber surface's surface charge be induced using chemical and mechanical techniques. A metal thiolate-based additive will be added to the chemical approach to activate the natural rubber's ionic sites. The latex band will be subjected to cyclic mechanical action to generate the surface charge, such as periodic stretching and relaxation. The increased surface charge of the latex band can create an electrostatic interaction with microplastic wastes in the water, allowing them to be captured and filtered out via attraction. The surface charge developed on the band will attract the oppositely charged microplastic and facilitate the capture. The NRL band will be manufactured via compounding and curing processes. The procedure for capturing microplastic wastes in seawater will be demonstrated in this work. Based on the results obtained, higher ZDEC loading produced better tensile properties and crosslink density than lower ZDEC loading. The tear strength of the NRL band using less ZDEC was slightly higher than that of the NRL band using more ZDEC. From FTIR and SEM results, it can be observed the presence of polypropylene and contaminant in the contaminated latex band. It can be concluded that the amount of ZDEC accelerator altered the mechanical characteristics of the NRL bands, enhancing microplastic capture.